Oral chronic graft-versus-host disease: analysis of dendritic cells subpopulations - Botari, Clara Marino Escpricigo; Nunes, Adauto José Ferreira; Souza, Mair Pedro de; Raduan, Érica Sinara Lenharo Orti; Salvio, Ana Gabriela [UNESP] (FapUNIFESP (SciELO), 2014)
The graft-versus-host disease is the major cause of morbidity and mortality in patients who have undergone hematopoietic stem cell transplantation. Aiming at contributing to the understanding of the role of myeloid and plasmacytoid dendritic cells, and natural killer cells in chronic graft-versus-host disease, we examined biopsies of jugal mucosa of 26 patients with acute myeloid leukemia who had undergone allogenic hematopoietic stem cell transplantation. Half of these patients developed oral chronic graft-versus-host disease. Microscopic sections were immunohistochemically stained for anti-CD1a, anti-CD123 and anti-CD56. We calculated the number of immunostained cells in the corium per square millimeter and applied the Mann-Whitney test. Results showed a statistically significant increase of myeloid dendritic cells (CD1a+; p=0,02) and natural killer cells (CD56; p=0,04) in patients with oral chronic graft-versus-host disease. CD123 immunostaining showed no statistical difference between groups. It was concluded that myeloid dendritic cells and natural killer cells participate in the development of oral chronic graft-versus-host disease.
Keywords: Células dendríticas; Doença enxerto contra hospedeiro crônica; Mucosa bucal